2023
DOI: 10.1371/journal.pone.0284515
|View full text |Cite
|
Sign up to set email alerts
|

Causes and characteristics of unexpected sudden cardiac death in octogenarians/nonagenarians

Abstract: Introduction The risk for sudden cardiac death (SCD) increases with ageing. Methods We evaluated causes and characteristics of unexpected SCD in SCD victims aged ≥ 80 years in a consecutive series of 5,869 SCD victims in Northern Finland. All the victims underwent medico-legal autopsy as medico-legal autopsy is mandatory in cases of unexpected sudden death in Finland. All the non-cardiac deaths such as pulmonary embolism and cerebral hemorrhage were excluded from the study, as were unnatural deaths such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient's clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older [9][10][11] In the studied group, there was a high prevalence of CKD patients (40%). Published studies suggest that these patients have a higher incidence of AKI 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age leads to several clinical and epidemiological differences between young and elderly patients. Even among the elderly, age groups should be considered in the patient's clinical management, since studies have shown differences in clinical profile and outcomes when comparing different age groups among patients aged 60 or older [9][10][11] In the studied group, there was a high prevalence of CKD patients (40%). Published studies suggest that these patients have a higher incidence of AKI 12 .…”
Section: Discussionmentioning
confidence: 99%